Healthcare Providers' Perspective about the Use of Telemedicine in Egypt: A National Survey. (12th March 2022) - Alboraie, Mohamed; Abdalgaber, Mohammad; Youssef, Naglaa; Moaz, Inas; Abdeen, Nermeen; Abosheaishaa, Hazem Maarouf; Shokry, Mina Tharwat; El-Raey, Fathiya; Asfour, Sabry Shaaban; Abdeldayem, Waleed A.; Hassan, Adel Ahmed; Mahran, Essam Eldeen M.o.; et al.
Abstract : Incorporation of telemedicine in general clinical practice is becoming a compelling need nowadays in the context of COVID-19 pandemic and its consequent burdens on the healthcare systems. Though telemedicine appears to be appealing and carries a lot of advantages, yet it is still faced by many challenges and barriers especially in developing countries. Our aim was to explore the impression of healthcare providers about telemedicine and its applicability in clinical practice in Egypt. A cross-sectional study was conducted among healthcare providers from different Egyptian governorates through a web-based survey. The survey gathered information about demographic, socioeconomic features of the enrolled healthcare participants; their knowledge, previous experience, impression about telemedicine, advantages of telemedicine over traditional medical services, barriers that may face telemedicine, and additional services that can be provided by telemedicine were also explored. Our study enrolled 642 healthcare providers from all over Egypt, 43.77% were females, of which 55.5% were physicians, 27.3% were nurses, 6.1% were technicians, 7.6% were administrative clerks, and 3.6% were medical directors. Sixty-four percent of participants reported that they have never used telemedicine. Smartphones were the most commonly used mean in the group who used telemedicine (65%), and smartphone applications were the favorable telemedicine service for about 50% of participants. Participants assumed that the use of telemedicine might not have a negative effect on the doctor-patient relationship but raised some concerns regarding the privacy and security of patients' data. Despite the fact that telemedicine appears to be appealing and widely accepted by healthcare providers, yet still, its implementation is confronted by some obstacles. Precise organizational guidelines need to be developed to clearly figure out the exact role of each healthcare provider to minimize their doubtfulness about telemedicine and to facilitate its adoption.